Development, physical-chemical stability and rheological behavior of silicones formulations containing Dimethylaminoethanol (DMAE) - Paula Souza Prestes, Roberta Balansin Rigon, Gustavo Narvaes Guimarães, Maria Luiza Ozores Polacow, Maria Silvia Mariani Pires-de-Campos, Marlus Chorilli, Gislaine Ricci Leonardi (Journal of Applied Pharmaceutical Science, 2013)
The aim of this paper was to develop formulations increased of DMAE and evaluate their physical-chemical stability and rheological behavior. Eleven formulations containing 3% DMAE pidolate or 3% DMAE acetamidobenzoate were developed and both preliminary stabilities tests and rheological measurements were carried out. They were considered stable during all period of study. The type of DMAE did not modify the viscosity of the emulsion and all presented pseudoplastic behavior with hysteresis area. An increase of hysteresis area could be observed with DMAE addition. The results point that the type of DMAE can influence the physical stability of the final product.
Keywords: Dimethyl MEA, Physical Stability, Cosmetic, Emulsion